The People First Network (Salomon Islands) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The People First Network (PFnet) has been instrumental in bringing connectivity to the Solomon Islands, where 85% of the population have no access to telecommunications.